Perceptions of Chinese hospital leaders on joint commission international accreditation: a qualitative study - Zhang, HongFan; Huang, Siou-Tang; Bittle, Mark J.; Engineer, Lilly; Chiu, Herng-Chia (Frontiers in Public Health, 2023)
Background: Joint Commission International (JCI) accreditation plays a significant role in improving the quality of care and patient safety worldwide. Hospital leadership is critical in making international accreditation happen with successful implementation.Little is known about how Chinese hospital leaders experienced and perceived the impact of JCI accreditation. This paper is the first study to explore the perceptions of hospital leaders toward JCI accreditation in China.Methods: Qualitative semi-structured interviews were used to explore the perceptions of the chief operating officers, the chief medical officers, and the chief quality officers in five JCI-accredited hospitals in China. Thematic analysis was used to analyze the interview transcripts and identify the main themes.Results: Fifteen hospital leaders participated in the interviews. Three themes emerged from the analysis, namely the motivations, challenges, and benefits related to pursuing -Bachelor